Negative transfer in second language writing among Malay university students / Fatin Nadirah Mohd Yusof - Fatin Nadirah , Mohd Yusof (2018)
Writing in any language presents a great challenge to most learners as it involves a complex cognitive activity and it is particularly harder if it involves bilingual or multilingual learners as it is said that the different languages have both positive and negative influence on the learners’ writing. The aim of this study is to investigate the phenomenon of negative transfer and the strategies employed in second language writing that cause negative transfer among Malay university students. The corpus of the study were 25 essays written by 25 participants. The participants are Malay university students with the same number of years of education through primary and secondary education in Malaysia. The instruments used for this study were participants’ written essays, questionnaire and oral interviews. All the errors in the essays were identified and classified into various categorizations. The results of the study showed that the types of Negative Transfer that occurred in the students’ essays are misinterpretation (MI), calques and substitutions from the Production Errors (PE) category. This study has shed light on the manner in which students experienced some interference from their first language and how it has posed problems when they are writing in their target language, which is English. However, the study is limited to only the aspect of writing. It is hoped that this study will offer new insights in improving the problematic writing aspects faced by the learners as well as developing and improving their overall writing performance.